Effect of solvent composition of electrospun PLGA fibers on paclitaxel release - Chen, Huizhi (2020)
Site-directed delivery of antimicrobial agents for inflammatory diseases showed significant medical advances, which can be realized through drug-loaded electrospun fibers. In this study, paclitaxel was applied as model hydrophobic drug, and the effect of solvent ratio on drug distribution and release kinetics would be discussed. It was found that different co-solvent ratios (9:1, 7:3, and 5:5, v:v) of chloroform and dimethylformamide could alter the resultant fiber diameter and morphology as well as paclitaxel release kinetics. Slower release was observed with higher ratio of chloroform. XPS results showed that this is primarily due to a better dispersion of paclitaxel in the fibers prepared from solvent ratio of 9:1 whereas the drug was found to accumulate on the surface for samples 5:5 and 7:3. Our results provided insight into the importance of solvent and solvent ratio not just in fabrication of required fibrous structure but also on release of active compounds.